GNOSISME DAN PENGARUHNYA TERADAP PEMIKIRAN PENDIDIKAN ISLAM - Dedi Sahputra Napitupulu (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
Nowadays, One of aspect of islamic education that get the more attention and evolve is tasawuf. The thought of suifsm actually is not only followed by muslims in east region, but it also gets the best place in west region. Eventhough, many historians accused that tasawuf became the most responsible factor and became the cause of  decline of islamic civilization , moreover it also becames vacum of all those. Actually tasawuf has carried out the important rule in muslims life generally and islamic education especially. This research was conducted by using descriptive analysis, those paragpraph will elaborate the development of Gnosisme in Islamic thought, figure and its monumental creation, also its influence toward islamic education’s though.